Challenges and Difficulties to Teaching Engineering to Generation Z: a case research - Barreiro, Suamit Correia (2017)
Many people from generation Z are at the beginning of their academic activities. This generation has peculiar characteristics that might be a challenge in the labor market. Thus, instructors have a great role in their preparation. However, professors might face difficulties dealing with their specific characteristics. The research aims to carry out a general survey to enable an understanding of the greater challenges and difficulties in teaching the subject of engineering to the students of Generation Z. The research method used was a case study at a University with 20 instructors from the Faculty of Engineering. The analysis revealed a great challenge in relating theoretical concepts with practical concepts. The research also showed a probable tendency of using more exhibition methods, and the low knowledge about generation Z by most instructors. This study seeks to contribute to the teaching-learning process of engineering.